Análise experimental e numérica do ensaio de tração por compressão diametral em concreto com brita calcária e granítica - Oliveira, Tales Renan Zacarias de (Universidade Federal Rural do Semi-Árido, 2020)
Due to the abundance of limestone rocks in the Northeast region, mainly in the states of Rio Grande do Norte and Ceará, it is attractive to study the use of this gravel as a coarse aggregate in structural concrete, for this, it is necessary to analyze the strokes with limestone gravel and plasticizer additive, to try to obtain a resistance close to or equivalent to the concrete with granite gravel. To find the tensile strength of concrete, three main tests are used, these are the tests of axial tensile, flexural tensile, and diametrical compression tensile. The diametrical compression tensile test is known worldwide as the Brazilian tensile test, as it was created by Prof. Fernando Luiz Lobo Carneiro, where we were able to indirectly find the tensile strength of concrete, through a relationship with its diametrical compression. Using studies by numerical methods, it is possible to numerically model destructible concrete tests. This work aimed to analyze the tensile behavior of concrete with limestone and granite gravel by means of experimental tests and numerical simulation. The experimental tests were carried out according to the current standards, then the computer software FEMAP® (Finit Element Modeling And Postprocesing) was used, in which simulations of the same experimental test were carried out and the concrete behavioral data was acquired. With the data acquired in the experimental and computer simulation tests by FEMAP®, a comparison was made with the analytical formulation of the traction problem by diametrical compression and relatively small errors were found in the requests obtained, presenting an effective option in carrying out tests. . Finally, the tensile strength parameters were obtained for concrete with limestone gravel with superplasticizer additive and granite gravel, confirming that there is a good tensile strength when using additives, but that it does not reach the strength of the concrete that uses the gravel granite as aggregate.
Keywords: FEMAP; Concreto; Elementos finitos; Tração por compressão diametral; FEMAP; Concrete; Finite elements; Diametrical compression traction; ENGENHARIAS::ENGENHARIA CIVIL